2022
DOI: 10.57604/prrs-005
|View full text |Cite
|
Sign up to set email alerts
|

National Breast Implant Registry in Italy. Competent Authority Perspective to Improve Patients’ Safety

Abstract: Conclusions. The pilot phase showed effectiveness in providing high-quality data thanks to the principles that drove its building. The pilot phase granted us further expertise and identified aspects that must be analyzed thoroughly. We rely on the immediate applicability of the registry's mandatory requirement to achieve a complete and effective tool that improves patients' safety and quality of our healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In 2019, the Italian Ministry of Health declared that there are no sufficient reasons to recommend the withdrawal from commercial availability of the textured implants. Moreover, the same Italian Ministry of Health affirmed that there is no indication to surgically remove the smooth or textured implant in the absence of clinical suspicion of BIA-ALCL [ 88 ]. It is strongly recommended to have a clear and transparent conversation with the patient, in order to inform her on the possible risks and benefits of each procedure, to achieve a shared decision to remove the implant and the periprosthetic capsule.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, the Italian Ministry of Health declared that there are no sufficient reasons to recommend the withdrawal from commercial availability of the textured implants. Moreover, the same Italian Ministry of Health affirmed that there is no indication to surgically remove the smooth or textured implant in the absence of clinical suspicion of BIA-ALCL [ 88 ]. It is strongly recommended to have a clear and transparent conversation with the patient, in order to inform her on the possible risks and benefits of each procedure, to achieve a shared decision to remove the implant and the periprosthetic capsule.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, recent studies have shown safety 22 , efficacy, and patient satisfaction following pre-pectoral breast reconstruction 23 ; however, further studies with longer follow-ups are needed to evaluate longterm outcomes. Mastectomy had increased in rate thanks to various factors such as better detection of multicentric tumors, widespread prophylactic mastectomies and improved quality of breast reconstruction [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive approach and local anaesthesia seem to better preserve immune functions; and should be preferred also for oncoplastic surgery with advantages in oncological and infectiology terms despite the lack of high-level evidence [33][34][35] . Conversion from local to general anaesthesia can be required due to anxiety and agitation although awake oncoplastic surgery was well tolerated by the patients with satisfaction at the end of the procedure.…”
Section: Discussionmentioning
confidence: 99%